Changes in cytomegalovirus load in the breast milk of very/extremely premature infants and the effect of pasteurization and freeze-thawing on reducing viral load - Tingting Huang; Tingting Huang; Wenhong Cai; Chen Ni; Shuhua Lai; Shuidi Lin; Quangui Wang (Frontiers Media S.A., 2022)
ObjectiveThis study aimed to clarify the change in Cytomegalovirus (CMV) loads in breast milk (BM) of very/extremely premature infants (VPI/EPI) with birth weight < 1,500 g after birth, and to compare the effectiveness of pasteurization and freeze-thawing methods in reducing the CMV load of BM.MethodsBreast milk samples were collected and tested every 2 weeks by fluorescence quantitative polymerase chain reaction (FQ-PCR). We determined CMV load in BM before and after pasteurizing, and freeze-thawing.ResultsCytomegalovirus DNA can already be detected in colostrum. The viral load gradually increased in the first 4 weeks, peaked in the 4th to 6th weeks, and gradually decreased thereafter. The viral load gradually returned to the initial level approximately 10-12 weeks postpartum. During the peak period of the CMV load in BM, the viral load was higher in the EPI than the VPI (P < 0.05). The average CMV load (logarithmic [LG]) in the pasteurization group was significantly lower than that in the raw BM group. The average CMV load in the freeze-thawed BM group was significantly lower than that in the raw BM group. The mean CMV load in the pasteurized BM group was lower than that in the freeze-thawed BM group, but the difference was not statistically significant. The CMV-DNA clearance rate in pasteurized was higher than in freeze-thawed (P < 0.05).ConclusionThe CMV detoxification rate in BM is high and the peak load period is mainly between 4 and 6 weeks. The CMV load values detected are higher than the threshold values (7 × 103 copy number/mL) of CMV infection that are reported in the literature as a concern. Both the freeze-thaw and pasteurization techniques can effectively reduce the CMV load.